2012
DOI: 10.1371/journal.pone.0037508
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of the Role of O-Glycosylations of Von Willebrand Factor

Abstract: The objective of this project was to study the function of O-glycosylations in von Willebrand factor (VWF) life cycle. In total, 14 different murine Vwf cDNAs mutated on one or several O-glycosylations sites were generated: 9 individual mutants, 2 doublets, 2 clusters and 1 mutant with all 9 murine glycosylation sites mutated (Del-O-Gly). We expressed each mutated cDNA in VWF deficient-mice by hydrodynamic injection. An immunosorbent assay with Peanut Agglutinin (PNA) was used to verify the O-glycosylation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 34 publications
(57 reference statements)
2
45
0
Order By: Relevance
“…29,[32][33][34] In addition, although the molecular mechanisms involved were not elucidated, enhanced VWF clearance has also been associated with loss of specific O-linked glycans. 30,58 In this paper, we demonstrate that complete loss of N-linked glycan expression following PNGase F digestion also results in markedly enhanced macrophage-mediated VWF clearance. Interestingly, recent studies have reported that N-linked glycan expression on factor X also plays a key role in regulating interaction with macrophages.…”
Section: Discussionmentioning
confidence: 69%
“…29,[32][33][34] In addition, although the molecular mechanisms involved were not elucidated, enhanced VWF clearance has also been associated with loss of specific O-linked glycans. 30,58 In this paper, we demonstrate that complete loss of N-linked glycan expression following PNGase F digestion also results in markedly enhanced macrophage-mediated VWF clearance. Interestingly, recent studies have reported that N-linked glycan expression on factor X also plays a key role in regulating interaction with macrophages.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have demonstrated that these polyclonal anti-human VWF antibodies cross-react with murine VWF and can be used to measure murine plasma VWF:Ag levels. 34,35 After blocking with 3% bovine serum albumin (BSA; Sigma-Aldrich) test samples were then added at appropriate dilutions. Bound murine VWF was detected using horseradish peroxidase-conjugated (HRP) rabbit anti-human VWF antibody (Dako).…”
Section: Determination Of Plasma Vwf:ag and Collagen-binding Activitymentioning
confidence: 99%
“…46 Notably, site-directed mutagenesis of Ser1486 to Ala resulted in normal VWF synthesis and multimerization but decreased VWF hemostatic function. 47 On the other hand, the substitution of Ser with Leu at 1486 is predicted to be "benign" at the protein sequence conservation level, while the substitution of Ser1486 with Ala is predicted to be "possibly damaging" by Polyphen2. Therefore, the putative mechanism of effect of the Ser1486Leu variant on lowering VWF:Ag remains to be determined.…”
Section: Vwf Missense Variants In African Americans 593mentioning
confidence: 99%